Development of Hybrid Approach for Receiver Location Privacy in WSN - B.S, Premananda; K.L, Sindhudhar (International Journal of Engineering and Technology, 2018)
The various security protocols in wireless sensor networks (WSNs) provide confidentiality for the content of message but the contextual information remains exposed. The exposed contextual information can be utilized by the adversary to deliver attack or derive the sensitive information such as location of the sink nodes, source node and monitored objects. In applications such as military and research institutions the security is of greater importance and very crucial. In sensor network the base station (BS) acts as a gateway between the sensor nodes and the control unit. The vital data sensed by the sensor nodes finally reaches the BS. Hence, BS is a major target of attack. By knowing the physical location of the BS an attacker can alter or destroy the BS intern results in the failure of the entire sensor network. There is a need for routing algorithm which can effectively camouflage the location of the BS. In this paper a hybrid algorithm which provides location privacy of the BS has been proposed. The results infer that the proposed algorithm is independent of quantity of the traffic and an adversary will have less than 4 % chance of locating the physical location of the BS. The sensor nodes also exhibited limited energy consumption.Â Â